Show and Tell: Exposing Anthroparchy in Children’s Culture: Review of Matthew Cole & Kate Stewart, Our Children and Other Animals: The Cultural Construction of Human-Animal Relations in Childhood - Hübben, Kelly (Humanimalia, 2019)
Matthew Cole & Kate Stewart, Our Children and Other Animals: The Cultural Construction of Human-Animal Relations in Childhood. Farnham: Ashgate, 2014. 195 pp. 100.00 hc; 43.96 pb; 49.46 e-book.